Survey of the intelligent and connected vehicle cybersecurity - Wufei WU; Renfa LI; Gang ZENG; Yong XIE; Guoqi XIE (Tongxin xuebao)
Cyber attacks on vehicles not only cause privacy leaks and economic losses but also endanger human life and even rise to national public safety issues.Therefore,the research on the cybersecurity of intelligent and connected vehicle (ICV) has become a research hot spot.Firstly,the structural status and characteristics of the in-vehicle network (IVN) in ICV were introduced,and the challenges and constraints of cybersecurity enhancement design for IVN were also presented.Secondly,focusing on the current functional safety and cybersecurity issues of IVN,a survey of the current cybersecurity enhancement researches for IVN was conducted.Finally,according to the characteristics of the IVN structure,some important research directions and suggestions about cybersecurity problems of ICV were pointed out from the three aspects of standard construction,functional safety and cybersecurity.